Pengaruh Job Insecurity, Job Stress, dan Work Environment Terhadap Turnover Intention Karyawan: Studi Kasus pada Karyawan di Kota Solo - Erliana Nur Rahmadiani; Kusdiyanto (Masyarakat Ekonomi Syariah Bogor, 2024)
Human resources are an important aspect of a company. Without qualified human resources, a company cannot achieve its goals properly. However, these human resources also need to be managed, so that they provide good performance. The management process is not easy, because it involves various elements, such as leaders, employees and the management system itself. Therefore, in a company, a problem called turnover intention often arises. This study tries to examine what influences turnover intention, such as in this study involving job insecurity, job stress, and work environment variables. This study used a sample size of 150 respondents, namely employees in Solo City. The non-probability sampling method uses purposive sampling method. Data collection using a questionnaire distributed via Google Form. Data analysis was carried out using Smart PLS 3.0. This study produces findings that job insecurity affects turnover intention, job stress affects turnover intention, and work environment has no effect on turnover intention.